2017
DOI: 10.1080/15213269.2017.1361842
|View full text |Cite
|
Sign up to set email alerts
|

Sexually Explicit Internet Material and Adolescents’ Sexual Performance Orientation: The Mediating Roles of Enjoyment and Perceived Utility

Abstract: Little is known about how exposure to sexually explicit Internet material (SEIM) relates to a performance-focused orientation toward sex. Based on a three-wave panel study among adolescents (N = 1,022), we found that watching SEIM predicted a sexual performance orientation from Wave (W) 2 to W3, but not from W1 to W2. A sexual performance orientation at W2 predicted adolescents' exposure to SEIM at W3. The relationship between exposure to SEIM and a sexual performance orientation was explained by a two-step… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3
2

Relationship

3
2

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 51 publications
3
18
0
Order By: Relevance
“…The more media users believe they can learn from or receive relevant information of a media source, the more willing they are to accept the messages promoted in the media source. Accordingly, the perceived utility of SEIM has been demonstrated to mediate the extent to which watching SEIM triggered a change in adolescents' sexual attitudes (Peter & Valkenburg, 2006Vandenbosch, van Oosten, & Peter, 2018). Similar findings have been reported in research on the mediating role of perceived realism in the relationship between the use of general entertainment media and instrumental attitudes toward sex (Chock, 2011).…”
Section: The Role Of Perceived Utility Of Seim and Instrumental Attitsupporting
confidence: 77%
See 2 more Smart Citations
“…The more media users believe they can learn from or receive relevant information of a media source, the more willing they are to accept the messages promoted in the media source. Accordingly, the perceived utility of SEIM has been demonstrated to mediate the extent to which watching SEIM triggered a change in adolescents' sexual attitudes (Peter & Valkenburg, 2006Vandenbosch, van Oosten, & Peter, 2018). Similar findings have been reported in research on the mediating role of perceived realism in the relationship between the use of general entertainment media and instrumental attitudes toward sex (Chock, 2011).…”
Section: The Role Of Perceived Utility Of Seim and Instrumental Attitsupporting
confidence: 77%
“…Future research may also consider a three-step mediation model including affective and cognitive state variables as well as an attitudinal variable preceding a behavioral outcome. In one recent paper, we found that the emotional state-type variable enjoyment of SEIM preceded the cognitive state-type variable perceived utility (Vandenbosch et al, 2018). As such, future research may combine the insights of the latter article suggesting an order exists in state-type variables (Vandenbosch et al, 2018), with the findings of the current paper on the order between attitudinal and behavioral outcomes.…”
Section: The Explanatory Value Of a Two-step Mediation Model With Attsupporting
confidence: 60%
See 1 more Smart Citation
“…In line with this reasoning, entertainment, social, and pornographic media have been identified as valuable sexual information sources by adolescents (Bleakley et al 2009;Ringrose 2009;Vandenbosch et al 2018). These media can contain positive or negative information about sexuality.…”
Section: Mediamentioning
confidence: 94%
“…Important differential susceptibility factors refer to developmental traits (e.g., age, puberty), social factors (e.g., family environment), and dispositional characteristics (e.g., sensation seeking, hyper gender identity) (Peter and Valkenburg 2016;Ward et al, 2013). Studies on response states have shown that sexual media effects often occur "indirectly" through processes, such as excitative (e.g., arousal) or cognitive (perceived utility of media content) responses (Peter and Valkenburg 2016;Vandenbosch et al 2018).…”
Section: Mediamentioning
confidence: 99%